The Chinese Export Displacement Effect Revisited - Christian Elleby; Wusheng Yu; Qian Yu (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2018)
China's global export share has increased dramatically over the past decades. This development has prompted an empirical literature on whether Chinese exports displace those originated from elsewhere in various destination markets. In this paper we focus on the growth of China's exports to the East African Community (EAC) countries and show how it has affected exports from the European Union (EU) to the EAC. Our main contribution to the literature on the displacement effect of Chinese exports is a set of total and relative displacement estimates based on different specifications of the gravity model where we control for country-year fixed effects so as to avoid the "gold medal mistake" of not accounting for time varying "multilateral resistance". Our findings do not support the hypothesis that Chinese exports have displaced exports from other countries in general. Nor do they support the hypothesis that Chinese exports have displaced exports from EU countries to the EAC countries or elsewhere. There has been no displacement in the sense that, although exporters from the EU and elsewhere have lost market share to China, the value of their exports to the EAC and elsewhere have still increased.
Keywords: F13; F14; F15; 330; habits; trade; gravity equation; export displacement; China; East African Community; European Union